Tannic acid(TA) protects against cadmium acetate induced toxicity in female rats (Role of tannic acid AS antioxidant) - Al-Fartosi, Khalid (University of Thi-Qar Journal of Science, 2010)
Cadmium is a highly toxic element that can be ingested or inhaled from a variety of industrial and dietary sources. Tannic acid (TA) is a plant polyphenol found in many dietary plant materials such as grain sorghum, coffee, tea and cocoa. The purpose of this study was to investigate the role of tannic acid against cadmium acetate induced toxicity in female rats.Three groups of adult female rats were treated orally with normal saline (0.09 Nacl) as a control group, 200 ppm cadmium acetate (first treated group), and 200 ppm + 200 ppm tannic acid (second treated group) for 12 weeks. The results indicated that cadmium acetate caused a significant decreased in RBCs count, Hb concentration, and PCV of female rats compared with control group, while that tannic acid enhanced these parameters. Also, the results showed that cadmium acetate induced a significant alternative in total and differential count of WBC, while these changes were attenuated by the tannic acid administration. Total protein and albumin were decreased significantly in female rats treated with cadmium, while there was non significant differences between these parameters in control female rats compared with Cd + TA treated rats. AST, ALT, ALP, Cholesterol, and TG were increased significantly in cadmium treated rats, but these values were decreased according to (TA) administration.